PENDEKATAN SCIENTIFIC DALAM PEMBELAJARAN TEMATIK TERPADU DI SD - Ali Armadi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
The characteristics of material scientific approach to learning materials based on facts or phenomena that can be explained by a certain logic or reasoning; teacher’s explanation, the response of learners and educational interaction teacher-learners free of prejudice necessarily, subjective thinking or reasoning which deviated from the groove to think logically; encourage and inspire students to think critically, analytically and precisely identify, understand, solve problems, and apply the learning materials; encourage and inspire students to think hypothetically in seeing the differences, similarities, and link to each other of learning materials; encourage and inspire students to understand, implement, and develop ways of thinking rationally and objectively in response to learning materials; based on concepts, theories and empirical facts that can be accounted for; learning objectives formulated in a simple, clear, and attractive presentation systems.